2020
DOI: 10.5829/ije.2020.33.04a.03
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Analytical Study on Alccofine Based High Strength Concrete

Abstract: The use of supplementary cementitious materials (SCMs) in concrete manufacturing is considered as financial, technical and environmental benefit. In this regard, this paper presents the experimental and analytical study of high strength concrete (HSC) with alccofine-1203 (alccofine) and fly ash as partial replacements to cement. A total of seven mixes were prepared with different percentages of alccofine (4-14%). The prepared concrete mixes were experimentally tested for slump, compressive, flexural and split … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Other studies have shown that direct mixing phase change material can greatly improve the hydration cycle, but affects the mechanical properties of cement paste / concrete [32]. Alccofine1203 has improved mechanical quality properties in high intensity concrete and green concrete [32][33][34] with a 10% integration. Direct incorporation of PCM in concrete had been studied primarily earlier.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies have shown that direct mixing phase change material can greatly improve the hydration cycle, but affects the mechanical properties of cement paste / concrete [32]. Alccofine1203 has improved mechanical quality properties in high intensity concrete and green concrete [32][33][34] with a 10% integration. Direct incorporation of PCM in concrete had been studied primarily earlier.…”
Section: Introductionmentioning
confidence: 98%
“…Active inclusion of PCMs in traditional building materials [30] allows PCMs uniformly distributed and often contributes to leakage and other problems [31]. Other studies have shown that direct mixing phase change material can greatly improve the hydration cycle, but affects the mechanical properties of cement paste / concrete [32]. Alccofine1203 has improved mechanical quality properties in high intensity concrete and green concrete [32][33][34] with a 10% integration.…”
Section: Introductionmentioning
confidence: 99%
“…It is a measure of the ability of concrete to withstand axial loads or forces that tend to squeeze or crush materials. Sagar and Sivakumar [23] observed a maximum 17 % improvement in compressive strength of conventional concrete. Pawar and Saoji [18] discovered that self-compacting concrete (SCC) containing 10 % alccofine-1203 had superior workability and compressive strength.…”
Section: Compressive Strengthmentioning
confidence: 96%
“…This increase may be due to inclusion of fillers in concrete diminish the voids by enhancing packing density and addition of fibre reduce crack growth and development of new cracks. https://www.indjst.org/ Based on the compressive strength, the replacement of cement with alccofine was beneficial upto 10% and further, 12% or 14% replacement levels falls in strength were observed compared to mix with10% alccofine (18) . Replacement of cement with 10% alccofine and iron powder enhanced the maximum compressive strength of 43.52 N/mm 2 , flexural strength of 5.1N/mm 2 respectively compared to the conventional concrete (19) .…”
Section: Compressive Strengthmentioning
confidence: 99%
“…The increases may be due to the effect of arbitrarily oriented PP fibres that produces the higher energy absorption. The increases in flexural strength to alccofine based mixes may be attributed due to strong bonding (ITZ) between the aggregates and cementitious materials (18) . The flexural strength of prism specimens made with and without polypropylene fibres are presented in Table 5.…”
Section: Modulus Of Rupturementioning
confidence: 99%